The melancholy science : an introduction to the thought of Theodor W. Adorno - Rose, Gillian (Macmillan, 1978)
"The Melancholy Science" is Gillian Rose s investigation into TheodorAdorno s work and legacy. Rose uncovers the unity discernableamong the many fragments of Adorno s oeuvre, and argues that hisinfluence has been to turn Marxism into a search for style. The attempts of Adorno, Lukacs and Benjamin to develop a Marxisttheory of culture centred on the concept of reification are contrasted, and the ways in which the concept of reification has come to bemisused are exposed. Adorno s continuation for his own time ofthe Marxist critique of philosophy is traced through his writings onHegel, Kierkegaard, Husserl and Heidegger. His opposition to theseparation of philosophy and sociology is shown by examination ofhis critique of Durkheim and Weber, and of his contributions to thedispute over positivism, his critique of empirical social research andhis own empirical sociology. Gillian Rose shows Adorno s most important contribution to be hisfounding of a Marxist aesthetic that offers a sociology of culture, asdemonstrated in his essays on Kafka, Mann, Beckett, Brecht andSchonberg. Finally, Adorno s Melancholy Science is revealed tooffer a sociology of illusion that rivals both structural Marxism andphenomenological sociology as well as the subsequent work of theFrankfurt School."